How do you simplify the product (6x - 5)(3x + 1)(6x−5)(3x+1) and write it in standard form?
2 Answers
Explanation:
"each term in the second bracket is multiplied by each"each term in the second bracket is multiplied by each
"term in the first bracket"term in the first bracket
=(color(red)(6x-5))(3x+1)=(6x−5)(3x+1)
=color(red)(6x)(3x+1)color(red)(-5)(3x+1)larrcolor(blue)"distribute"=6x(3x+1)−5(3x+1)←distribute
=(color(red)(6x)xx3x)+(color(red)(6x)xx1)+(color(red)(-5)xx3x)+(color(red)(-5)xx1)=(6x×3x)+(6x×1)+(−5×3x)+(−5×1)
=18x^2color(blue)(+6x)color(blue)(-15x)-5larrcolor(blue)"collect like terms"=18x2+6x−15x−5←collect like terms
=18x^2-9x-5larrcolor(magenta)"in standard form"=18x2−9x−5←in standard form
Try using the FOIL method (First, Outside, Inside, Last)
Explanation:
You have to multiply each term in the left bracket by each term in the right bracket. The easiest way to make sure you don't miss anything is to use a systematic method such as FOIL.
The FOIL method means selecting those pairs of numbers to multiply together
Eg.
Question
First:
Outside:
Inside:
Last:
Now we add them together
leaving us with